TEKNOLOGI SEPARATOR PADA BATERAI LI-ION: MATERIAL, TEKNIK FABRIKASI, DAN UJI PERFORMA - Nikolas Krisma Hadi Fernandez; Farid Triawan (Media Mesin: Majalah Teknik Mesin, 2023)
The trend of using electric vehicles is increasing. With the increasing use of electric vehicles, it is necessary to master the key technologies used by electric vehicles, one of which is batteries, especially lithium-ion batteries (LiB). There are many important components in the LiB, one of which is a separator that serves to block short circuits between the anode and cathode of the battery while providing a way for ion exchange to continue. This article summarizes important information related to battery separator technology. The information includes the materials that have been used in commercial products and those of under research and development. In addition, the method of fabricating the separator using conventional methods and 3D printing is discussed. Finally, this article also discusses how several studies perform performance tests on separator materials. Keywords: battery separator, fabrication, materials, performance test, lithium-ion battery.